Life Cycle Assessment of Aquaculture Systems: Environmental Hotspots, Methodological Challenges, and Pathways Towards Sustainable Production - Arakkal, Razia Mohamed; Samuel, Manoj P.; Das, Dhiju P. H.; Edwin, Leela; Madhu, V. R.; Jha, Paras Nath; Ninan, George (Fishery Technology, 2026)
Aquaculture has become a critical contributor to global food and nutritional security; however, its rapid expansion has raised concerns regarding resource use, emissions, and ecosystem degradation. Life Cycle Assessment (LCA), standardized under ISO 14040/14044, has emerged as a key framework for quantifying the environmental impacts of aquaculture systems across diverse species, production technologies, and geographic contexts. This review synthesizes 105 peer-reviewed LCA studies to evaluate environmental hotspots, methodological practices, and emerging trends in aquaculture sustainability assessment. Comparative analysis reveals that feed production and energy consumption dominate environmental impacts, particularly global warming potential, eutrophication, and acidification, irrespective of species or culture intensity. While intensive and closed systems such as recirculating aquaculture and biofloc technologies enhance water and nutrient management, they often incur higher climate impacts due to elevated electricity demand. Significant methodological variability exists across studies, particularly in the selection of functional units, system boundaries, allocation procedures, and treatment of uncertainty, limiting cross-study comparability and hence the relevance of decision making. Critical gaps are also identified in the assessment of biodiversity, disease-related impacts, and dynamic system behaviour. Building on these findings, the review outlines future directions for aquaculture LCA, emphasizing renewable energy integration, sustainable aquaculture feed development, circular economy strategies, and the incorporation of emerging tools such as dynamic LCA, social LCA, artificial intelligence, and planetary boundary frameworks. By consolidating the existing and current knowledge and identifying priority research needs, the review provides a robust foundation for advancing environmentally resilient and resource-efficient aquaculture systems aligned with global sustainability goals.